2021
DOI: 10.1210/jendso/bvaa203
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of SARS-CoV-2 Infection Associated With Pituitary Apoplexy Without Comorbidities

Abstract: Pituitary apoplexy is a medical and surgical emergency caused by hemorrhage or infarction of the hypophysis, which typically occurs within a pituitary adenoma. It is usually characterized by severe (often thunderclap) headache, visual disturbances, cranial nerve impairments, and hormonal deficiencies. We herein report a case of a previously healthy woman with severe acute respiratory syndrome coronavirus 2 infection associated with pituitary apoplexy. The plausible pathophysiological mechanisms of pituitary ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…To the best of our knowledge, four cases have been reported so far in the English literature. [ 8 , 10 , 19 , 21 ] We herein report the fifth case of this association. Although the available information is limited, analyzing the pertinent literature is important to gain further insight on whether the PA is directly caused by COVID-19 infection and to come up with plausible pathophysiological mechanism(s) if any.…”
Section: Introductionmentioning
confidence: 91%
“…To the best of our knowledge, four cases have been reported so far in the English literature. [ 8 , 10 , 19 , 21 ] We herein report the fifth case of this association. Although the available information is limited, analyzing the pertinent literature is important to gain further insight on whether the PA is directly caused by COVID-19 infection and to come up with plausible pathophysiological mechanism(s) if any.…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, the virus has been hypothesized to enter the brain through the nasopharyngeal epithelium via the olfactory nerve, or could pass through the blood-brain barrier or directly reach the median eminence, a circumventricular organ where the blood-brain barrier is lacking [59]. In fact, recently, several cases of pituitary apoplexy associated with COVID-19 mainly in the context of pre-existing macroadenomas were reported (Table 1) [60][61][62][63][64][65].…”
Section: Pituitary Apoplexymentioning
confidence: 99%
“…Ghosh et al reported a case of a 44-year-old woman admitted to the ED with complaints of a sudden-onset severe headache and progressive asymmetric visual blurriness, symptoms preceded by abrupt-onset intermittent fever [61]. Cognitive and cranial nerve functions were intact except for subtly asymmetric bitemporal hemianopic visual field defects.…”
Section: Pituitary Apoplexymentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent case of a 44-year-old healthy woman with undiagnosed pituitary macroadenoma, presenting with concomitant COVID-19 infection requiring hospitalisation and pituitary apoplexy has been published. 9 Again, the authors draw on both the physical location of COVID-19 infection giving advantage to CNS infection, as well as likely endothelial dysfunction, platelet derangement, coagulopathy and the understood fragility of the pituitary vasculature as possible explanations for this clinical scenario.…”
Section: Discussionmentioning
confidence: 99%